Understanding self-compassion in adolescents: Validation study of the Self-Compassion Scale - Cunha, Marina (2016)
Self-compassion is an adaptive self-attitude when considering personal inadequacies or difficult life situations and seems to be crucial to adolescent’s experience. However, self-compassion remains less investigated in adolescence. This paper aims to analyse the psychometric properties of Self-Compassion Scale (SCS; Neff, 2003) and test its six-factor structure through a Confirmatory Factor Analysis in a representative sample of adolescents. The sample consists of 3165 adolescents, aged between 12 and 19 years old (Mage = 15.49) from Portuguese schools. Results confirm the six-factor and second-order structures of the SCS and the measurement invariance across gender. The SCS and subscales also revealed good internal reliability and convergent validity with measures of positive emotional memories, depressive, anxiety and stress symptoms. Overall, our findings suggest that the SCS is a valid and reliable measure to assess self-compassion among adolescents.